Climate change governance, Shariah governance quality, and financed emission mitigation: Evidence from Islamic banks in Southeast and West Asia - Issa, Saheed Olanrewaju; Alabi, Abdulkadri Toyin; Ubandawaki, Abdulbaki Teniola (Borsa Istanbul Anonim Sirketi, 2025)
The financial sector holds major responsibility in climate mitigation, as the proliferation of environmental damage within the real economy largely stems from the negative externalities of the financial economy. Islamic banking, as a subset of the global financial market, is often adjudged as a promoter of ethical practices. This study investigates how climate governance mechanisms and Shariah governance quality influence Islamic banks’ mitigation of financed emissions. Data was obtained from the LSEG database and the annual reports of 28 sampled Islamic banks covering the period of 2019–2023. The results of logistic regression indicate that sustainability committees, sustainability reporting, and Shariah governance quality positively affect financed emission mitigation in Islamic banks. This study therefore recommends for Islamic banks to adopt robust climate governance mechanisms, as well as for regulators to institutionalize policies mandating sustainable finance.